Investigation of ICOS, CD28 and CD80 polymorphisms with the risk of hepatocellular carcinoma: a case–control study in eastern Chinese population. Issue 7 (5th July 2019) - Yang, Jing; Liu, Jiaochun; Chen, Yu; Tang, Weifeng; Bo, Kai; Sun, Yuling; Chen, Jianping
Abstract : Single nucleotide polymorphisms (SNPs) in immune related gene may influence the susceptibility of cancer. We selected inducible T cell costimulator ( ICOS ) rs4404254 T>C, rs10932029 T>C, CD28 rs3116496 T>C and CD80 rs7628626 C>A SNPs and assessed the potential relationship of these SNPs with hepatocellular carcinoma (HCC) risk. A total of 584 HCC cases and 923 healthy controls were recruited. And SNPscan™ genotyping assay was used to obtain the genotypes of ICOS, CD28 and CD80 polymorphisms. We found that ICOS rs10932029 T>C polymorphism significantly increased the risk of HCC (additive model: adjusted odds ratio (OR), 1.59; 95% confidence interval (CI), 1.13–2.22; P =0.007; homozygote model: adjusted OR, 1.12; 95% CI, 0.31–4.03; P =0.867; dominant model: adjusted OR, 1.58; 95% CI, 1.14–2.19; P =0.007 and recessive model: adjusted OR, 1.02; 95% CI, 0.28–3.68; P =0.974). However, ICOS rs4404254 T>C, CD28 rs3116496 T>C and CD80 rs7628626 C>A SNPs were not associated with the risk of HCC. To evaluate the effects of ICOS rs10932029 T>C on HCC risk according to different age, gender, chronic hepatitis B virus (HBV) infection, tobacco consumption and drinking status, we carried out a stratification analysis. We found that ICOS rs10932029 T>C polymorphism might increase the risk of HCC in male, ≥53 years, never smoking, never drinking and non-chronic HBV infection subgroups. Our study highlights that ICOS rs10932029 T>C polymorphism may confer the susceptibility to HCC. It may be beneficial to explore the relationship between variants in immune related genes and the development of HCC.